Improved spatial reuse algorithm for bandwidth management and scheduling in IEEE 802.16j relay networks - Gundimeda Abhay Krishna. (2011)
The final year project is based on the research in IEEE 802.16j relay networks. The IEEE 802.16 standard introduced an additional relay mode in 2007 permitting coverage extension of the Point-to-Multipoint based WiMAX networks. Relays are invaluable in increasing the overall throughput and coverage. Such a relay enhanced network can provide excellent radio coverage and also achieves very high QoS requirements. Bandwidth management and scheduling algorithms, though, have been studied in some detail in the traditional IEEE 802.16 PMP networks, studies in the relay networks is still ongoing. Spatial reuse in the relay network is an especially interesting topic to study. In this FYP, the IEEE 802.16j relay network model has been studied greatly and existing scheduling algorithms for it have also been covered. Various algorithms and mathematical equations involved in the model are presented in this report. This project proposes an improved spatial reuse algorithm which builds on a previous research to improve spatial reusability in the relay network. It shows experimentally with the help of a custom simulator the benefits of using the improved algorithm.